Continuously thermal conductive pathway of bidisperse boron nitride fillers in epoxy composite for highly efficient heat dissipation. (June 2021) - Kim, Jun Min; Jung, Dae-Woong; Kim, Lee Su; Kim, Myungsu; Jeong, Sooyeol; Lee, SangGap; Chang, Sung-Jin; Cho, Jung Young; Kim, Sun Ha; Park, Joon Yong; Choi, Kyuseok; Yi, Gi-Ra; et al.
Graphical abstract: Highlights: A BN surface was non-covalently functionalized by benzoic acid. An alkaline epoxy resin induced hydrogen bonding of benzoic acid on BN. The Farris effect and hydrogen bonding were responsible for improved κ. Abstract: This study presents a combined strategy of bidisperse boron nitride (BN) and surface modification to improve the thermal conductivity ( κ ) of the BN-epoxy composite. Surface modification of hexagonal BN was carried out with benzoic acid (BA). The optimal weight ratio of large and small BN (BN l and BN s ) was 8:2 for their connectivity in the epoxy matrix. For 50 wt% filler content, the BN l 8 s 2 -BA composite has a much higher κ of 2.71 W/m K (out-plane direction), which is 12.3, 1.32, and 1.50 times higher than that of the pure epoxy, and its composite with BN l 10 s 0 -BA and BN l 8 s 2, respectively. The chemical-sensitive analyses indicate that carboxyl-carboxylate interaction occurred in partially deprotonated benzoic acid on BN during the epoxy curing process, resulting in in-situ formation of a continuously thermal conductive pathway, which is responsible for the improved κ .